Accuracy of Ultrasonographic Measurements of Kidney Dog for Clinical Use - Barrera, Rafael; Duque, Javier; Ruiz, Patricia; Zaragoza, Concepción (Revista Científica de la Facultad de Ciencias Veterinarias, 1970)
The aim of this study was to determine the accuracy of ultrasonographic measurement of canine kidneys. A method agreement analysis comparing pairs of measurements (ultrasonographic kidney dimensions and direct kidney dimensions) was performed. Nineteen dogs aging from one to thirteen years were used. The ultrasonographic and anatomic linear parameters obtained from the kidneys were the following: width, length and height; the kidney volume was estimated from these measures using the formula of an ellipsoid. The statistical method performed (method agreement) demonstrated a satisfactory agreement. It can be concluded that ultrasound measurement is sufficiently accurate for clinical use, assuming a careful scanning technique.